The effects of reforms to the Work Capability Assessment for incapacity benefits - Sam Ray-Chaudhuri; Tom Waters (Institute for Fiscal Studies (IFS), 2023)
We investigate the potential impacts of the government's proposed reforms to the Work Capability Assessment.
Keywords: 330; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Disability; Government spending; Universal credit; Working age benefits; Poverty